Surface modification of ultrafine silicon nitride powders by calcination. Issue 4 (28th March 2019) - Ni, Zhentao; Yang, Xianfeng; Yang, Xiaole; He, Qinglong; Xu, Xiewen; Xie, Hehan
Abstract: Calcination was used for surface modification of ultrafine silicon nitride powders, which improved the flowability and dispersion stability of their slurries. Surface characteristics of the powder were investigated by X‐ray photoelectron spectroscopy, which showed the generation of an oxide layer and partial elimination of amine groups on the particle surfaces. Ion analysis results suggested a drop in both ion conductivity and supernatant concentration after calcination. For the as‐received powder, poor flowability and dispersion stability was caused by high‐valence cations, which were detrimental to colloidal processing according to the Schulze–Hardy rule, and surface amine groups were also present; both of these were partly removed by calcination. The oxide layer formed on the particle surfaces hydrolyzes into silanol groups when the powder is dispersed in aqueous solutions, which was favorable for surface charging and formation of higher diffuse layer potential on the particles. These factors contributed to the improved flowability and dispersion stability of the slurries. Abstract : Characteristics after calcination: (a) viscosity curves of slurries; (b) ion conductivity and concentration;(c) Si 2p peak deconvolution of Si3 N4 powder; (d) TEM graph of Si3 N4 powder.